2006
DOI: 10.1049/ip-cdt:20045130
|View full text |Cite
|
Sign up to set email alerts
|

Gigabyte per second streaming lossless data compression hardware based on a configurable variable-geometry CAM dictionary

Abstract: A high-throughput lossless data compression IP core built around a CAM-based dictionary whose number of available entries and data word width adjust to the characteristics of the incoming data stream is presented. These two features enhance model adaptation to the input data, improving compression efficiency, and enable greater throughputs as a multiplicity of bytes can be processed per cycle. A parsing mechanism adjusts the width of dictionary words to natural words while the length of the dictionary grows fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…To the best of our knowledge, we first have achieved an over-GB/s peak decompression bandwidth as a rule-based compression approach. For reference, the fastest circuit as a dictionarybased compression approach has already achieved an over-GB/s peak decompression bandwidth (1.092 GB/s) at the fabrication of a 130-nm technology node [21]. We have confirmed that our DPC decompression circuit, which is designed for a 40-nm DRP product, successfully loads actual test configurations to the product.…”
Section: B Data Rule Automationsupporting
confidence: 75%
“…To the best of our knowledge, we first have achieved an over-GB/s peak decompression bandwidth as a rule-based compression approach. For reference, the fastest circuit as a dictionarybased compression approach has already achieved an over-GB/s peak decompression bandwidth (1.092 GB/s) at the fabrication of a 130-nm technology node [21]. We have confirmed that our DPC decompression circuit, which is designed for a 40-nm DRP product, successfully loads actual test configurations to the product.…”
Section: B Data Rule Automationsupporting
confidence: 75%
“…It is obvious that the amount of debug data one can acquire is limited by the capacity of trace buffers. As a result, trace compression techniques (e.g., [21]- [26]) were proposed to compress debug data on-chip before being stored into trace buffers (Label 2). More recently, data restoration techniques were proposed to improve functional observability [27], [28].…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…The compared circuits are an advanced X-Match circuit [Nunez-Yanez and Chouliaras 2006], which has achieved an over-GB/s peak decompression bandwidth (1.092 GB/s) as a dictionary-based compression approach, and a GZIP circuit [AHA 2009], which has the second highest decompression bandwidth (see Figure 8). For reference, we add a 130-nm DPC decompression circuit to the table since the X-Match circuit is fabricated at a 130-nm technology node.…”
Section: Decompression Bandwidthsmentioning
confidence: 99%